(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
Today, the issue of improving the digital literacy of the population is being actively raised. This primarily concerns pupils, who have the highest demand for the use of digital technologies and internet capabilities in learning and everyday life. Pupils who develop digital literacy as an integral part of their education are more effective in their studies and are more in demand when it comes to employment.